Genomic characterization of vancomycin-resistant enterococci in Norwegian poultry - Rikki Franklin Frederiksen; Anne Margrete Urdahl; Jannice Schau Slettemeås; Silje Granstad; Roger Simm; Karin Lagesen (PLoS ONE, 2025)
Vancomycin resistant enterococci (VRE) are a globally leading cause of nosocomial infections in humans, and a potential animal VRE reservoir, especially in poultry, is of concern. It has been suggested that the presence of VRE in broilers has been prolonged due to co-selection of narasin resistance (narAB genes) and vancomycin resistance (vanA genes), and that these genes may be present on the same plasmids. The aim of this study was to use whole genome sequencing to characterize and compare both the chromosomes and plasmids of VRE isolates from poultry in Norway, and to elucidate whether co-localisation of narAB and vanA genes on the same genetic elements, or clonal spread, could explain the persistence of VRE. A total of 30 VRE isolates from the years 2002–2013 were included, 23 from broiler flocks and seven from turkey flocks. WGS analyses showed that the isolates were genetically diverse with the number of SNPs ranging from 10 to 2807. The isolates belonged to 15 different sequence types, though all carried a plasmid similar to pVEF plasmids, and contained both vanA and narAB. A comparative gene analysis indicated that narAB is carried on a composite transposon, and that interspecies transfer of the plasmid between Enterococcus faecium and Enterococcus hirae may occur. The absence of transfer genes on the pVEF-like plasmids and their presence on a megaplasmid suggest that the megaplasmid probably act as a helper plasmid. Overall, the results support that the use of narasin in broilers may be a risk factor for a persistent reservoir of VRE in broilers.